Metallocages for Metal Anions: Highly Charged [Co@Ge9]5− and [Ru@Sn9]6− Clusters Featuring Spherically Encapsulated Co1− and Ru2− Anions. Issue 37 (21st August 2019) - Witzel, Benedikt J. L.; Klein, Wilhelm; Dums, Jasmin V.; Boyko, Marina; Fässler, Thomas F.
Abstract: Endohedral clusters count as molecular models for intermetallic compounds—a class of compounds in which bonding principles are scarcely understood. Herein we report soluble cluster anions with the highest charges on a single cluster to date. The clusters reflect the close analogy between intermetalloid clusters and corresponding coordination polyhedra in intermetallic compounds. We now establish Raman spectroscopy as a reliable probe to assign for the first time the presence of discrete, endohedrally filled clusters in intermetallic phases. The ternary precursor alloys with nominal compositions "K5 Co1.2 Ge9 " and "K4 Ru3 Sn7 " exhibit characteristic bonding modes originating from metal atoms in the center of polyhedral clusters, thus revealing that filled clusters are present in these alloys. We report also on the structural characterization of [Co@Ge9 ] 5− (1a ) and [Ru@Sn9 ] 6− (2a ) obtained from solutions of the respective alloys. Abstract : Attraction despite repulsion : A formally two‐fold negatively charged anion, Ru 2−, is encapsulated inside the cavity of the anionic metallocage [Sn9 ] 4− . The highly charged [Ru@Sn9 ] 6− anion can be crystallized in salts from liquid ammonia solutions of a K‐Ru‐Sn alloy. The encapsulated atoms lead to characteristic Raman modes which allow the detection of filled clusters in the respective alloys.